Optimización de la QoE de un servicio de vídeo streaming en un entorno celular - Mendoza Ruiz, Jéssica; Herrera-García, Ana; Palacios, David; De la Bandera Cascales, Isabel; Barco-Moreno, Raquel (My University, 2018)
The rising traffic demand in mobile communications networks, as well as the increase in the number of available services and the expectations of users have led operators to seek new techniques to optimize mobile networks. In this way, traditional optimization techniques, based on improving the quality of service offered to users, have given way to new techniques based on improving the quality of experience (QoE) perceived by users. In this work, a study to improve the QoE perceived by the users in a real time video streaming service from the optimization of the transmission buffer size of the RLC (Radio Link Control) layer is presented. The optimization, which has been carried out in a simulated cellular environment, has been performed for two different system bandwidth values, thus proving the relationship between the quality perceived by the users, the optimal buffer size and the available bandwidth.
Keywords: Aplicaciones para móviles; Sistemas telefónicos móviles